Trending Technologies: A Corpus-based Genre Analysis of Abstracts on ChatGPT - Emmanuel Mensah Bonsu; Dorah Kwakyewaa Adusei (Linguistics Initiative, 2023)
Genre studies have dominated academic contexts, with a particular focus on research article abstracts. Such studies have focused on single and cross-discipline discourse practices, rather than how different disciplines address a common subject based on its communicative purpose. Against this backdrop, this study conducted a corpus-based genre analysis of RA abstracts on ChatGPT. Synergising ESP textual analysis, and corpus-based analysis, the study analysed 72 abstracts. The analyses revealed the ‘Product’ and ‘Purpose’ moves were the most frequent in the abstracts. The ‘Product’ move was afforded much textual space. Concerning the lexicogrammatical features, chatgpt was typified in all the abstracts, occurring frequently at the ‘Introduction’ and ‘Purpose’ moves. Furthermore, the potential and use of ChatGPT, as well as its educational implications, were themes developed from the lexicogrammatical characteristics. Based on these findings, the study provides recommendations for practice and further research.